2021
DOI: 10.1038/s41598-020-80850-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SSRI exposure on the proliferation rate and glucose uptake in breast and ovary cancer cell lines

Abstract: Breast cancer is the most prevalent malignancy amongst women worldwide while ovarian cancer represents the leading cause of death among gynecological malignancies. Women suffering from these cancers displayed heightened rates of major depressive disorder, and antidepressant treatment with selective serotonin reuptake inhibitors (SSRIs) is frequently recommended. Recently, narrative reviews and meta-analyses showed increased recurrence risks and mortality rates in SSRI-treated women with breast and ovarian canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 57 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…Similarly, a recent meta-analysis by Li et al reviewed 19 studies, finding no causal relationship [ 73 ]. And breast cancer cell line research has shown no significant effect of SSRIs on cell glucose uptake [ 74 ]. Indeed, other work has even suggested that such medications may even be used to positive effect.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a recent meta-analysis by Li et al reviewed 19 studies, finding no causal relationship [ 73 ]. And breast cancer cell line research has shown no significant effect of SSRIs on cell glucose uptake [ 74 ]. Indeed, other work has even suggested that such medications may even be used to positive effect.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study indicated that use of paroxetine is associated with a substantial increase in breast cancer risk [ 29 ]. A recent study also reported that women with breast and ovarian cancer receiving SSRIs exhibit increased recurrence risks and mortality rates [ 30 ]. Conversely, some SSRIs can induce apoptosis in Burkitt lymphoma cells by triggering calcium flux, tyrosine phosphorylation and reduction of the c-myc and nm23 genes [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously indicated how the multifactorial etiopathogenesis of depression makes not only the diagnosis and treatment of this entity difficult, but also prevention remains complex, and numerous studies must be carried out in order to analyze different preventive interventions in cancer patients to improve the quality of life and reduce the incidence of depression and anxiety associated with this entity. In this sense, numerous studies have shown how psychopharmacological drugs in cancer can have effects on cancer patients at different biological levels and can be another tool for the comprehensive management of these patients (186)(187)(188).…”
Section: D) Psychosocial Interventionsmentioning
confidence: 99%